The Impact Of Smartphones On Work Productivity As Perceived By Employees At A Government Department In Salalah, Oman - Fraj AlZwamri, A.A.; Hussain, N. (Universiti Sains Islam Malaysia, 2024)
This paper elaborates the study on the impact of smartphones in a public department in Salalah, Oman. It highlights how the smartphone technology which came into existence nearly ten years ago has caused drastic changes in the field of communication. Smartphones have been developing rapidly and are increasingly integrated in people's lives. The impacts of smartphone usage in the workplace may be positive or negative which may influence work productivity in any organization. In this article, the impacts of smartphones on employees work performance were identified and the mechanism of dealing with these impacts are described in order to help, develop and increase their productivity or work performance.